Associations between human bacterial pathogens and ARGs are magnified in leachates as landfill ages. (February 2021) - Wu, Dong; Wang, Liuhong; Su, Yinglong; Dolfing, Jan; Xie, Bing
Abstract: Landfills constitute the largest treatment and disposal reservoirs of anthropogenic waste on earth and they are continuously releasing antibiotic resistance genes (ARGs) to the environment for decades via leachates. Little is known about the association between ARGs and human bacterial pathogens as a function of time. Here, we quantified 10 subtypes of ARGs, integrons, and human bacterial pathogens (HBPs). Except for the ARGs encoding resistance to sulfonamides, the subtypes encoding resistance to beta-lactams, macrolides, and aminoglycosides were not related to integrons (Spearman, P  > 0.05). Over time presence of ARGs became increasingly more correlated with the presence of human bacterial pathogens (Procrustes test; R  = 0.81, P  < 0.05), which were primarily identified as the Proteobacteria, Actinobacteria, and Firmicutes . Rather than the prevalence of integrons, dynamics of the bacterial community, including the increased nitrogen metabolism activity of Proteobacteria and decreased bacterial diversity were assumed to lead to a magnified association between HBPs and target ARGs (Varpart; > 13%). Graphical abstract: Image 1 Highlights: Target ARGs became increasingly associated with pathogens in leachates. Integrons were not directly related to the enhanced "pathongen-ARGs" associations. Bacteria with higher N-metabolizing capacity outcompeted other phyla in leachates. Pathogens are more likely to acquire ARGs in a less diverse bacterial community.